2021
DOI: 10.3390/cancers13215475
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Treatment Paradigm for Hepatocellular Carcinoma Using Atezolizumab plus Bevacizumab Combination Therapy

Abstract: Atezolizumab plus bevacizumab combination therapy was approved worldwide for use in 2020. A 30% objective response rate with 8% complete response (CR) was achieved in a phase 3 IMbrave150 trial. Here, the change in the treatment strategy for hepatocellular carcinoma (HCC) using atezolizumab plus bevacizumab combination therapy is reviewed. The phase 3 IMbrave150 clinical trial was successful because of the direct antitumor effect of bevacizumab, which shifted the suppressive immune microenvironment to a respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…In this study, there was a significantly higher conversion rate in the ATEZO/BEVA group than in the LEN group. Kudo reported that when significant tumor reduction occurred, the strategy of ATEZO/BEVA followed by curative conversion (ABC conversion) was possible [ 23 ]. In particular, patients with intermediate-stage HCC who are not suitable for TACE may benefit the most [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was a significantly higher conversion rate in the ATEZO/BEVA group than in the LEN group. Kudo reported that when significant tumor reduction occurred, the strategy of ATEZO/BEVA followed by curative conversion (ABC conversion) was possible [ 23 ]. In particular, patients with intermediate-stage HCC who are not suitable for TACE may benefit the most [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kudo reported that when significant tumor reduction occurred, the strategy of ATEZO/BEVA followed by curative conversion (ABC conversion) was possible [ 23 ]. In particular, patients with intermediate-stage HCC who are not suitable for TACE may benefit the most [ 23 ]. In conversion cases in the ATEZO/BEVA group, nine patients (69.2%) were diagnosed with intermediate-stage HCC and were unsuitable for TACE.…”
Section: Discussionmentioning
confidence: 99%
“…The role of bevacizumab is thought to transform suppressive immune microenvironments into responsive ones. For these reasons, even in the presence of the WNT/β-catenin mutation, there are cases in which the therapeutic effect of atezolizumab plus bevacizumab therapy could be expected [26]. Regarding atezolizumab plus bevacizumab therapy for heterogeneous or hyperintense types HCC, it may be necessary to make an early judgment of tumor response in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al reported on the usefulness of a combination therapy (cisplatin monotherapy and sorafenib) [28]. We also previously reported on the efficacy of combination therapy with TACE or HAIC and lenvatinib [29], and Kudo et al reported the importance of conversion treatment after atezolizumab plus bevacizumab combination therapy [30]. These reports suggest that multidisciplinary treatment combining systemic and locoregional treatments, including HAIC, might be the best therapeutic strategy for the management of advanced HCC.…”
Section: Discussionmentioning
confidence: 86%